2020
DOI: 10.1098/rspa.2020.0469
|View full text |Cite
|
Sign up to set email alerts
|

Electrocharged facepiece respirator fabrics using common materials

Abstract: Face masks in general, and N95 filtering facepiece respirators (FRs) that protect against SARS-Cov-2 virion in particular, have become scarce during the ongoing COVID-19 global pandemic. This work presents practical design principles for the fabrication of electrocharged filtration layers employed in N95 FRs using commonly available materials and easily replicable methods. The input polymer is polypropylene or polystyrene, and can include discarded plastic containers of these materials, and the fabrication set… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…Once in contact, the particles adhere to the fiber via van der Waals attraction and remain stuck. [ 59 , 62 , 63 ]…”
Section: Standards Testing Methods and Efficacy Of Face Masksmentioning
confidence: 99%
“…Once in contact, the particles adhere to the fiber via van der Waals attraction and remain stuck. [ 59 , 62 , 63 ]…”
Section: Standards Testing Methods and Efficacy Of Face Masksmentioning
confidence: 99%
“…Thus, along with the size-assisted filtration by the pore and inertial impaction, the electrostatic attraction-assisted filtration is also found to be occurring in PPY layers. Such masks have efficiency at the 95% level as respiratory masks to protect even from virus and bacteria [ 16 ]. But, it has been found that the charge on the PPY fabrics does not hold for more than 8 h upon exposure to the ambient conditions and hence, such masks drastically decrease in efficiency after such a short period [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we test various low-cost mask systems alongside popular medical and high-performance masks such as N95 masks. N95 masks use electrostatic filtration to trap particles [1]. Sars-CoV2 has amino acids that are chemically attached to sugars which can be charged, and is negatively charged at a neutral pH [1].…”
Section: Introductionmentioning
confidence: 99%
“…N95 masks use electrostatic filtration to trap particles [1]. Sars-CoV2 has amino acids that are chemically attached to sugars which can be charged, and is negatively charged at a neutral pH [1]. Thus, electrostatic surfaces like that of an N95 mask trap virus particles very effectively, adding an extra layer of filtration beyond the physical barriers of a mask [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation